Value and importance of informed consent to researchers at Makerere University - Ochieng, Joseph (Annals of Tropical Medicine and Public Health, 2012)
Respect for persons requires that research participants be given the opportunity to make choices about what should be done to them. Many times, the process of informed consent is abused to the benefit of researchers while exploitation and harm to the research participants may occur. In Uganda, issues of questionable research ethics have been highlighted in the past. Objective: To determine the Value and importance of the informed consent process among researchers at Makerere University. Materials and Methods: This was a qualitative descriptive study design involving faculty and graduate students in the faculties of Medicine and Social Sciences. Results: Of the 37 respondents 68% were faculty while 32% were graduate students in the fields of social sciences, clinical and basic sciences. Mean research experience was 8.5 years. More than 70% of the respondents have had no formal training in research ethics. Only 22% of the respondents appreciated the need for research participants to comprehend the informed consent; 38% thought it is not always the case and in many cases their subjects do not have to comprehend, while the remaining 40% believe that research subjects’ understanding of the informed consent process may not be necessary. All respondents appreciated the importance of confidentiality although data management procedures were lacking by many. Conclusion: Most researchers appreciate the importance of confidentiality, but have limited understanding of the process of informed consent, information handling and the importance of feedback.
Keywords: Importance; Informed consent; Makerere university; Researchers; Value